Psalms 73-150 - Estes, Daniel J. 1953- (Nashville, Tennessee : B & H Publishing Group, 2019)
The New American Commentary is for the minister or Bible student who wants to understand and expound the Scriptures.
Dan Estes's new work on the Psalms is an exceptional addition to this valuable series. Not only is he extremely qualified to write such a work because much of his scholarly work has been done in the Psalms for more than three decades, but he is also qualified by his love for the church, which will be aided greatly by his present work. This commentary on one of the most beloved books in the Old Testament is very thorough. It deals with current debates in the Psalms and yet is practical for gaining insights into the meaning of each of the psalms. Especially helpful will be the Response section for each of the psalms that provides clear guidance on how to apply the psalm for today. --Paul D. Wegner, Distinguished Professor of Old Testament, Gateway Seminary of the Southern Baptist Convention.
Editor's Preface -- Author's Preface -- Abbreviations -- Book III: Psalms 73-89 -- Book IV: Psalm 90-106 -- Book V: Psalms 107-150 -- Bibliography -- Author Index -- Scripture Index.
Includes bibliographical references (pages 639-651) and indexes.
Keywords: Bible. -- Commentaries; Commentaries; Commentaries